The two different isoforms of the RSC chromatin remodeling complex play distinct roles in DNA damage responses. - Anna L Chambers; Peter M Brownlee; Samuel C Durley; Tracey Beacham; Nicholas A Kent; Jessica A Downs (PLoS ONE)
The RSC chromatin remodeling complex has been implicated in contributing to DNA double-strand break (DSB) repair in a number of studies. Both survival and levels of H2A phosphorylation in response to damage are reduced in the absence of RSC. Importantly, there is evidence for two isoforms of this complex, defined by the presence of either Rsc1 or Rsc2. Here, we investigated whether the two isoforms of RSC provide distinct contributions to DNA damage responses. First, we established that the two isoforms of RSC differ in the presence of Rsc1 or Rsc2 but otherwise have the same subunit composition. We found that both rsc1 and rsc2 mutant strains have intact DNA damage-induced checkpoint activity and transcriptional induction. In addition, both strains show reduced non-homologous end joining activity and have a similar spectrum of DSB repair junctions, suggesting perhaps that the two complexes provide the same functions. However, the hypersensitivity of a rsc1 strain cannot be complemented with an extra copy of RSC2, and likewise, the hypersensitivity of the rsc2 strain remains unchanged when an additional copy of RSC1 is present, indicating that the two proteins are unable to functionally compensate for one another in DNA damage responses. Rsc1, but not Rsc2, is required for nucleosome sliding flanking a DNA DSB. Interestingly, while swapping the domains from Rsc1 into the Rsc2 protein does not compromise hypersensitivity to DNA damage suggesting they are functionally interchangeable, the BAH domain from Rsc1 confers upon Rsc2 the ability to remodel chromatin at a DNA break. These data demonstrate that, despite the similarity between Rsc1 and Rsc2, the two different isoforms of RSC provide distinct functions in DNA damage responses, and that at least part of the functional specificity is dictated by the BAH domains.